(untitled) (Swiss Medical Weekly, 2018)
Over the last few years, there have been many changes in the management of patients with follicular lymphoma, resulting in improvements in progression-free survival and quality of life. In addition to established regimens such as radiotherapy and immunochemotherapy, new treatment options are on the horizon. Furthermore, even the use of established chemotherapy agents has evolved, with new combinations moving to the forefront of the current treatment strategy. Nevertheless, there remains an unmet need for patients who have early relapses, those who are not responsive to anti-CD20 treatment regimens and for those in whom minimal residual disease persists even after immunochemotherapy. This review provides a summary of current developments in the diagnosis, treatment and management of follicular lymphoma, focusing on the clinical issues from a Swiss perspective.